Long-term events after physician-referred initial tests by myocardial perfusion imaging or computed tomography coronary angiography in patients with suspected coronary artery disease. Issue 7 (November 2018) - Naya, Masanao; Uemura, Yukari; Matsumoto, Naoya; Momose, Mitsuru; Kato, Takao; Hida, Satoshi; Yamauchi, Takao; Nakajima, Takatomo; Suzuki, Eriko; Tamaki, Nagara
Abstract : Background: The effects of initial tests on long-term events have been unknown. Patients and methods: In this observational retrospective study, we analyzed the effects of initial noninvasive tests by myocardial perfusion imaging (MPI) and computed tomography angiography (CTA) on long-term major adverse cardiac events (MACEs) among patients with suspected coronary artery disease during a median follow-up of 8.1 years (interquartile range: 7.7–8.9). Results: Sex difference in the rate of abnormal findings on initial tests was observed in both the MPI (female vs. male: 32.6 vs. 55.5%; P <0.0001) and CTA groups (30.6 vs. 47.9%; P <0.0001). Early revascularization in the MPI was significantly lower than that in the CTA (16 vs. 23%; P =0.0005). A total of 109 MACEs (39 of 1830 patients during the original follow-up period and 70 of 616 patients during the extended follow-up period) occurred: 77 MACEs (6.4%) in the MPI group and 32 (5.1%) in the CTA group (adjusted hazard ratio for MPI: 0.78; 95% confidence interval: 0.50–1.23; P =0.29). In the total cohort, the risk-adjusted MACE rate in the females was ∼50% of the males. Conclusion: The long-term MACE rates did not differ between physician-referred initial tests of MPI and CTA despite a higher frequency of early revascularization in the CTA group. In this extended cohort, female sex was associated with a lower rate of positive findings and a lower MACE rate compared with the male sex.